2017
DOI: 10.1200/jco.2017.35.15_suppl.4008
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II study of PEGPH20 plus nab-paclitaxel/gemcitabine (PAG) vs AG in patients (Pts) with untreated, metastatic pancreatic ductal adenocarcinoma (mPDA).

Abstract: 4008 Background: Hyaluronan (HA) accumulation in the tumor microenvironment produces elevated tumor pressure, vascular compression, and reduced drug delivery. PEGPH20 degrades HA, increasing the access and therapeutic index of anticancer agents. Methods: In Stage 1 of this phase II study, pts with untreated mPDA were randomized 1:1 to PAG (P; 3 µg/kg IV 2x/wk x 3 wks in C1, then 1x/wk x 3 wks in C2+, plus AG) vs AG every 28 days. An imbalance in thromboembolic (TE) events in the PAG arm led to a clinical hold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
0
22
0
2
Order By: Relevance
“…Auf dem ASCO und ESMO 2017 wurden nun die Ergebnisse der randomisierten HALO-202-Studie vorgestellt. Diese Phase-I/II-Studie vergleicht die Kombination aus Gemcitabin und nab-Paclitaxel ± PEGPH20 in der palliativen Erstlinientherapie [41,42]. Primärer Endpunkt der Studie war das progressionsfreie Überleben und als zusätzlicher primärer Sicherheits-Endpunkt die Rate an thromboembolischen Ereignissen bei bekannter Risikozunahme unter PEGPH20-Therapie.…”
Section: Pankreaskarzinom: Tumorstroma Als Zielunclassified
“…Auf dem ASCO und ESMO 2017 wurden nun die Ergebnisse der randomisierten HALO-202-Studie vorgestellt. Diese Phase-I/II-Studie vergleicht die Kombination aus Gemcitabin und nab-Paclitaxel ± PEGPH20 in der palliativen Erstlinientherapie [41,42]. Primärer Endpunkt der Studie war das progressionsfreie Überleben und als zusätzlicher primärer Sicherheits-Endpunkt die Rate an thromboembolischen Ereignissen bei bekannter Risikozunahme unter PEGPH20-Therapie.…”
Section: Pankreaskarzinom: Tumorstroma Als Zielunclassified
“…tumorigenesis, survival, metastasis, multiclonality, etc.). The potential for GEMM in advancing PDA therapies is demonstrated by the development of PEGPH20 for enhancing tumoral delivery of cytotoxics, originally tested in the KPC model, which has shown promise in clinical trials for HA-high PDA patients 30,98 .…”
Section: Pancreas Cancer Modelsmentioning
confidence: 99%
“…Multiple preclinical and clinical studies have demonstrated that targeting the biophysical barrier to drug delivery in PDA with PEGPH20 is both feasible and promising. 12,25,34,37 Results from both the phase Ib 34 and phase II (HALO-202) 38 clinical trials have demonstrated that the administration of PEGPH20 with different cytotoxic chemotherapy combinations is feasible and effective.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…38 To date, there have been no studies investigating PEGPH20 as monotherapy in PDA. All studies have investigated PEGPH20 used in combination with chemotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation